Securitización y condicionalidad migratoria en la ayuda oficial al desarrollo de la Unión Europea - Delkáder-Palacios, A. (Revista Iberoamericana de Estudios de Desarrollo)
In this article, it is explained the consequences of migration-related conditionality for the EU development policy which appears after a process of securitization of migration. In this way, it contributes to a better understanding of the security-migration-development nexus in the European Union (EU). For this, two key documents are critically reviewed to understand the external axis of the EU migration policy, such as the European Agenda on Migration and the Partnership Framework with third countries. In the study it is concluded that migration-related conditionality redirects development policy to objectives which are alien to it. In addition, these imposed objectives are in contradiction with some of the most important consensus of the global development agenda.